Argentina's Model of Accumulation: Twenty Years of Ruptures and Continuities - Fal, Juan (Social justice, 2013)
The article provides an overview of the major changes in Argentina's model of accumulation, economic policies, and their impact on the living conditions of the different social classes under the government of Argentinean President Nestor Kirchner, from 2003-2010. Topics discussed include end to neoliberalism, presence of high levels of poverty and inequality, and foreign penetration of capitalist factions without increases in employment and wages.